2022
DOI: 10.3390/v14081597
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Changes in the Deformed Wing Virus Population in Honey Bees Associated with the Introduction or Removal of Varroa destructor

Abstract: Varroa destructor is an ectoparasitic mite associated with significant losses of honeybee colonies globally. The mite vectors a range of pathogenic viruses, the most important of which is the Deformed wing virus (DWV). In the absence of Varroa, DWV exists as a low-level, highly diverse virus population. However, when transmitted by Varroa, certain variants become highly elevated, and may become near-clonal and cause symptomatic infections. Mite transmission between colonies can occur when parasitised workers d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 40 publications
3
19
0
1
Order By: Relevance
“…This shift in virus dominance has been reported at a landscape scale in multiple studies recently, including in the UK and the USA, suggesting that this is not a phenomenon associated with coordinated mite treatment (Kevill et al, 2019;Paxton et al, 2022;Ryabov et al, 2017). Experiments run in parallel with this study showed that mite infested colonies contained mixed populations of viruses, but that Type B variants were increasing over time (Woodford et al, 2022). A general shift from Type A to Type B has been observed across the UK (Kevill et al, 2021) sustained transmission of that variant.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This shift in virus dominance has been reported at a landscape scale in multiple studies recently, including in the UK and the USA, suggesting that this is not a phenomenon associated with coordinated mite treatment (Kevill et al, 2019;Paxton et al, 2022;Ryabov et al, 2017). Experiments run in parallel with this study showed that mite infested colonies contained mixed populations of viruses, but that Type B variants were increasing over time (Woodford et al, 2022). A general shift from Type A to Type B has been observed across the UK (Kevill et al, 2021) sustained transmission of that variant.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have suggested that low mite numbers do not necessarily translate to low DWV levels and colonies could still collapse in the winter, despite treatment application (Highfield et al, 2009). In this study, no colonies were reported to have very high DWV levels with low mite numbers (Figure S3), and our recent studies have clearly demonstrated that effective miticide treatment of colonies with high Varroa and virus levels resulted in massive reductions of the viral load within 4 weeks (Woodford et al, 2022). Interestingly the average titre of DWV across the island did not significantly decrease between 2017 and 2019, despite the drop in average mite levels (Figure 3a and Figure 4).…”
Section: Discussionsupporting
confidence: 51%
“…Each parameter in the model, whether that parameter is fixed or variable and where the information for the criteria originates from. The number in parenthesis in the left column indicates where each parameter occurs in the schematic shown in figure 2.parameterfixed or variablerationaleviruses in bee1000based on RT-qPCR analysis of healthy bees [15,16]virus diversity in bee3 variantsDDD / VVV / VVD used in passage experimentVarroa virus acquisition (1)5–505–42 dengue copies in mosquitões [24]virus amplification in mite (2)10 4 –10 7 RT-qPCR data [33]virus injection by mite (3)10 2 –10 5 0.1–100% of virus amplification in mite [33]virus amplification in next bee (4)10 6 –10 9 based on pupal injections [21]…”
Section: Methodsmentioning
confidence: 99%
“…This has been inferred to mean that viruses preferentially amplified after mite transmission end up dominating the virus population, reflected in a decrease in diversity. However, more recent research has indicated that individual bees infected with high titres of DWV often contain diverse virus populations [13][14][15] and the factors that determine why a population retains or loses diversity is unknown. One possibility is that particular virus genotypes may have a replicative advantage; there are two major genotypes (A and B) which also freely recombine [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…These above-mentioned factors caused a weakened immune system of pollinators and more susceptibility to the ingress of unwanted guests especially like: Nosema spp., Varroa destructor and other diseases such as rot ( Paenibacillus larvae ), viruses (deformed wings virus), etc. [ 4 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%